CHINA-PAKISTAN ECONOMIC CORRIDOR (CPEC): MAGPOONDAS SPECIAL ECONOMIC ZONES IMPACT ON FUTURE ECONOMY OF GILGIT-BALTISTAN - Asif Mehdi; Inayat Hussain; Abrar Hussain; Muhammad Ismail (International Journal of Contemporary Issues in Social Sciences, 2024)
The Magpoondas Special Economic Zones (SEZs), created as part of the China-Pakistan Economic Corridor (CPEC), might have a big impact on Gilgit-Baltitan’s economy in the future. The goal of these SEZs is to serve as important centers for business and industrial activity, supporting regional economic expansion, employment creation, and technical improvement. Because of its advantageous location and the infrastructure development made possible by CPEC, Gilgit-Baltistan is positioned to play a significant role in the larger economic framework. Origin direct investment, technological transfer, and improved commercial connectivity are anticipated outcomes of the Magpoondas Special Economic Zones. The possible benefits of this economic inflow include increased living standards, less unemployment, and economic diversification for the community. A robust and sustainable economic ecology in Gilgit-Baltistan may also be fostered by the creation of these SEZs, which may encourage innovation and skill development. To ensure the region's sustainable development, however, the environmental and social effects must be carefully taken into account. In order to maintain Gilgit-Baltistan's distinct cultural and biological legacy while promoting economic progress, community involvement, environmental conservation initiatives, and inclusive policies are essential. To sum up, the Magpoondas Special Economic Zones (SEZs) within the CPEC concept provide Gilgit-Baltistan prospects for revolutionary economic growth. However, cautious and comprehensive approaches are crucial to optimize advantages and minimize possible drawbacks.